PELUANG DAN TANTANGAN PENGEMBANGAN TEKNOPOLITAN DALAM MENINGKATKAN DAYA SAING INDONESIA - Sucia Miranti (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2016)
The biggest challenge facing by Indonesia today as the impact of Globalization is the challenge that comes from the economic sector, one possible cause is the imbalance of population growth which then led to unemployment and poverty. The unemployment rate in Indonesia reached 7.03 million in 2016 and will likely continue to increase if no action is taken to overcome various parties in Indonesia. This occurs when the Global Competitiveness Rep ort 2016 published by the World Economic Forum states that Indonesia is ranked 37 of 138 countries,it can be interpreted Indonesia has a better competition than the countries with fairly advanced economy such as Portugal and Spain. This indicates that there has been no solid match between education, technology, the labor market and the active role of various parties such as the government and society. Method used in this paper is a qualitative method that is expected to provide input and suggestions in order to improve Indonesia's ability to resolve the challenges of globalization, especially in the economic field. Based on the results of research and data processing can be concluded that by increasing the role of government and various elements of society through the application of triple helix theory which is realized in the embodiment Teknopolishit will be able to reduce unemployment and improve Indonesia's competitiveness to facing the globalization.